The Function of Necroptosis and Its Treatment Target in IBD - Francis Atim Akanyibah; Yi Zhu; Tao Jin; Dickson Kofi Wiredu Ocansey; Fei Mao; Wei Qiu (Mediators of Inflammation)
Inflammatory bowel disease (IBD), which encompasses Crohn’s disease (CD) and ulcerative colitis (UC), is a complicated illness whose exact cause is yet unknown. Necroptosis is associated with IBD pathogenesis, leading to intestinal barrier abnormalities and uncontrolled inflammation. Molecules involved in necroptosis, however, exhibit different expression levels in IBD and its associated colorectal cancer. Multiple studies have shown that inhibiting these molecules alleviates necroptosis-induced IBD. Moreover, due to the severe scarcity of clinical medications for treating IBD caused by necroptosis, we review the various functions of crucial necroptosis molecules in IBD, the stimuli regulating necroptosis, and the current emerging therapeutic strategies for treating IBD-associated necroptosis. Eventually, understanding the pathogenesis of necroptosis in IBD will enable the development of additional therapeutic approaches for the illness.